Reverse logistics adoption and firm's - Nik Abdullah, Nik Ab. Halim; Yaakub, Sabariah; Abdullah, Haim Hilman (Universiti Utara Malaysia, 2012)
One of the new challenges faced by Malaysian firms that want to go global is the fact that many countries have introduced legislation or directives to ensure effective disposal of manufactured products and its waste. Furthermore, the increase in awareness on environmental issues, sustainable development, corporate citizenship and the benefit of recycling had also placed more pressure on firms to adopt sustainable business initiatives such as a better reverse logistics strategy. Manufacturing firms however often focused on forward logistics and as a result, they tend to overlook at the importance of reverse logistics activities.The objective of this study is to look at the current level of reverse logistics adoption among manufacturers in Malaysia and to identify the influence of customer/stakeholder pressure, regulatory pressure, financial and competitive pressure, and corporate citizenship pressure on the level of reverse logistics adoption.In addition, this study also aims to determine the relationship between reverse logistics adoption level and firm’s performance.Data was collected through survey questionnaire, and the respondents consist of manufacturing firm managers located in the Northern State of Malaysia and the Klang Valley.Data analysis was conducted using both SPSS and Partial Least Square (PLS) regression analysis. Findings indicate that the level of reverse logistics adoption among Malaysia manufacturers is still low.The regulatory pressure has a significantly strong influence on the level of reverse logistics adoption, while customer/stakeholder pressure has moderate influence.No significant relationship was observed between the level of reverse logistics adoption and firm’s performance.